From ‘gaze’ to engage: Exploring Digital Technology Usage in North Norwegian Museum Narratives in relation to Tourism Experiences and Imaginaries - Udaya, Eman (UiT The Arctic University of Norway, 2020)
Museums are important heritage sites, cultural institutions, and tourist attractions. They hold a special authoritative status in providing legitimacy and authentic representation of art, artefacts, history, people, and cultures. The entry of digital technology in the museum space has brought forward numerous possibilities and complexities. Through this study, I will explore the use of digital technology in the narratives of three museums in Northern Norway. Taking into consideration the background and context of these museums and focusing on three main examples (two exhibitions and apps), I will discuss how museum narratives, through interactivity and digital staging mediated by digital technology, enhances experiences by inviting the visitors to engage and co-create instead of passively ‘gaze’. The discussion on representation of minority cultures of Sámi and Kven people in the museum space is also made. In this case, digital technology in museum narratives, on one hand, contributes to the revitalization process by promoting visibility, knowledge preservation and dissemination, and inclusion; while on the other hand, lack of ‘self-representation’ and collaboration poses a risk of promoting unequal power relations, and retaining stereotypical, ‘emblematic’ touristic image of the minority groups. The process results in making an impact on the ‘pre-tour’, ‘on-tour’ and ‘post-tour narratives’ and tourism imaginaries of Northern Norway. Consequently, by analysing the practical limitations, challenges, and complexities of using digital technology in the museum, this study brings to light the balanced relationship of digital and non-digital objects in museum narratives.